Economic Oligarchy and Environmental Damage in the Indonesian Pulp and Paper Industry - Lustania CAnjani; Ramada Ayudyra; Meylyana Zulfanabil; Nauvalla Adhivya; Iradhad Sihidi (Renewable Energy Issues, 2026)
This study examines the relationship between economic oligarchic structures and environmental degradation in Indonesia’s pulp and paper industry through a case study of PT Indah Kiat Pulp and Paper, part of the Sinar Mas Group. It aims to explain how concentrated corporate power shapes environmental governance and facilitates the externalization of ecological and social costs. The study applies Jeffrey A. Winters’ oligarchy theory and a political economy of environment approach to analyze power concentration and regulatory influence. Using a qualitative case study design, data were collected through document analysis of government policies, corporate sustainability reports, scientific publications, environmental organization reports, and secondary data on deforestation, pollution, and social conflicts in the company’s operational areas. The findings reveal that corporate economic dominance enables significant influence over environmental policy formulation and implementation, resulting in formalistic regulations and weak enforcement. Environmental costs are externalized through large-scale deforestation, waste pollution, and the marginalization of affected local communities. These outcomes indicate that environmental degradation is not merely a consequence of technical management failures but a structural effect of oligarchic economic configurations that constrain effective environmental governance. The study recommends governance reforms emphasizing transparency, accountability, strengthened public oversight, and broader community participation to promote ecological sustainability and social justice.